Plant-derived antivirals against hepatitis c virus infection - Gomes Jardim, Ana Carolina [UNESP]; Shimizu, Jacqueline Farinha [UNESP]; Rahal, Paula [UNESP]; Harris, Mark (Biomed Central Ltd, 2018)
Hepatitis C virus (HCV) infection is a worldwide public health burden and it is estimated that 185 million people are or have previously been infected worldwide. There is no effective vaccine for prevention of HCV infection; however, a number of drugs are available for the treatment of infection. The availability of direct-acting antivirals (DAAs) has dramatically improved therapeutic options for HCV genotype 1. However, the high costs and potential for development of resistance presented by existing treatment demonstrate the need for the development of more efficient new antivirals, or combination of therapies that target different stages of the viral lifecycle. Over the past decades, there has been substantial study of compounds extracted from plants that have activity against a range of microorganisms that cause human diseases. An extensive variety of natural compounds has demonstrated antiviral action worldwide, including anti-HCV activity. In this context, plant-derived compounds can provide an alternative approach to new antivirals. In this review, we aim to summarize the most promising plant-derived compounds described to have antiviral activity against HCV.
Keywords: Hepatitis C; Natural compounds; Antivirals